Contenido nutricional de alimentos y bebidas publicitados en la franja infantil de la televisión colombiana (2019)
ABSTRACT: To describe the nutritional content of foods and non-alcoholic beverages advertised in the children’s frame vs. the general frame in two national, private, free-access, television channels in Colombia. Methods: Cross-sectional, descriptive study. The recording was performed in July of 2012, for four days randomly chosen from 6:00 am to 12:30 pm. The nutritional content was classified according to the nutritional profiles criteria of the Food Standards Agency for risk-indicating nutrients, the Health Pan-American Organization for trans fat, and the 333 Colombian Resolution of 2011 that classifies foods as source of protecting nutrients. Descriptive statistics were used, the Kolmogorov-Smirnov test to establish the normality, and the Chi square test for variables comparison. A p value < 0.05 was considered. Results: During 52 hours of recording, 1560 commercialswere shown, of which 23.3% (364), advertised foods and beverages, of which 56.3% were shown within the children’s frame. Regarding the nutritional content, a high percentage of foods and non-alcoholic beverages classified as “rich” in sugar, sodium, saturated fat was observed within the children’s’ frame (69.0%, 56.0%, 57.1%), as compared to the general frame. By contrast, the percentage of foods and non-alcoholic beverages classified as “rich” in total fat was higher in the general frame as compared to the children’s frame (70.4% vs. 29.6%, respectively). Conclusions: Higher exposure to advertising of foods and non-alcoholic beverages was observed within the children’s’ frame, characterized by high content of risk-indicating nutrients and low content of foods and non-alcoholic beverages with protective nutrients.